Analysis of City Energy Systems Modeling Case Studies: A Systematic Review - Gupta, Kushagra; Ahlgren, Erik O. (International Journal of Sustainable Energy Planning and Management, 2025)
Cities are adopting energy planning strategies and emission reduction targets in line with national decarbonization targets. Modeling and scenario assessments are used to support energy planning. City energy systems are complex systems including interactions and interdependencies, as well as the specifics of the local city context. To investigate the representation of city-specific system complexities in existing case studies, a systematic literature review methodology is applied, and model applications are analyzed using a comparative analysis framework. Additionally, research objective themes used to define the specific aims are explored. Key modeling characteristics include scale aspects, method description, system definition, scenario formulation, and case-specific model inputs. The findings of this study suggest that city case studies have a diverse representation of modeling approaches. However, the analysis of model characteristics shows a limited representation of modeling features, such as stakeholder participation and local air pollution impacts that are unique to the urban context. In terms of research objective themes behind the model application, four research themes are identified. Studies aimed at identifying pathways to future low-carbon energy systems and evaluating policy impacts on the city energy systems are the most stated research objective themes for modeling city energy systems.